Pemberdayaan Masyarakat melalui Program Volly Ball Club dalam Mengembangkan Potensi Keolahragaan di Desa Tenggulun - Fatmawati, Hilda; Musthofa, R. Zainul; Aminah , Siti; Ramadona, Nadiyah; Islahuddin, Ahmad Thoriqul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2024)
Tenggulun is one of the villages in Solokuro District, Lamongan City. The people in Tenggulun village are a group Social society. They have enough insight and awareness High in sports. Sport can be used as development tHuman potential, character and active role in social life.Sport has benefits in all fields in society Such as education, culture, social, economy and health. Humans havePreoccupied with pragmatism activities at this time. They are sufficient Understand that moving is very important for health and being a treasureThe most valuable they could have. Health groupedInto four types, healthy physically, spiritually, socially and economically.Lack of physical activity and exercise will have an effectWhich is not good for the body. The Tenggulun people who haveIntense activity can do some physical activity for just thatRelax muscles and improve blood circulation such as: Morning walk,Sweeping floors, gotong royong in the village every few months and Other. If you have enough free time someone can Exercising. Types of sports that can be done in the environment The people of Tenggulun Village include gymnastics Aerobics, soccer, volleyball and leisure walks. Sports too Has benefits for physical fitness, achieving physical health Spiritual, social and economic in humans